BODIPY-based fluorescent liposomes with sesquiterpene lactone trilobolide - Škorpilová, Ludmila; Rimpelová, Silvie; Jurášek, Michal; Buděšínský, Miloš; Lokajová, Jana; Effenberg, Roman; Slepička, Petr; Ruml, Tomáš; Kmoníčková, Eva; Drašar, Pavel B.; Wimmer, Zdeněk (Beilstein Journal of Organic Chemistry, 2017)
Like thapsigargin, which is undergoing clinical trials, trilobolide is a natural product with promising anticancer and anti-inflammatory properties. Similar to thapsigargin, it has limited aqueous solubility that strongly reduces its potential medicinal applications. The targeted delivery of hydrophobic drugs can be achieved using liposome-based carriers. Therefore, we designed a traceable liposomal drug delivery system for trilobolide. The fluorescent green-emitting dye BODIPY, cholesterol and trilobolide were used to create construct 6. The liposomes were composed of dipalmitoyl-3-trimethylammoniumpropane and phosphatidylethanolamine. The whole system was characterized by atomic force microscopy, the average size of the liposomes was 150 nm in width and 30 nm in height. We evaluated the biological activity of construct 6 and its liposomal formulation, both of which showed immunomodulatory properties in primary rat macrophages. The uptake and intracellular distribution of construct 6 and its liposomal formulation was monitored by means of live-cell fluorescence microscopy in two cancer cell lines. The encapsulation of construct 6 into the liposomes improved the drug distribution in cancer cells and was followed by cell death. This new liposomal trilobolide derivative not only retains the biological properties of pure trilobolide, but also enhances the bioavailability, and thus has potential for the use in theranostic applications.
Keywords: BODIPY conjugates; cancer targeting; drug delivery; liposomes; natural compounds; sesquiterpene lactone trilobolide

(untitled) - Allen, T. M.; Cullis, P. R. (Adv. Drug Delivery Rev., 2013)

(untitled) - Pattni, B. S.; Chupin, V. V.; Torchilin, V. P. (Chem. Rev., 2015)

Application of Nanotechnology in Drug Delivery - Çağdaş, M.; Sezer, A. D.; Bucak, S. (Liposomes as Potential Drug Carrier Systems for Drug Delivery, 2014)

(untitled) - Kelkar, S. S.; Reineke, T. M. (Bioconjugate Chem., 2011)

(untitled) - Liu, Y.; Lok, C.-N.; Ko, B. C.-B.; Shum, T. Y.-T.; Wong, M.-K.; Che, C.-M. (Org. Lett., 2010)

(untitled) - Courtis, A. M.; Santos, S. A.; Guan, Y.; Hendricks, J. A.; Ghosh, B.; Szantai-Kis, D. M.; Reis, S. A.; Shah, J. V.; Mazitschek, R. (Bioconjugate Chem., 2014)

(untitled) - Verbelen, B.; Boodts, S.; Hofkens, J.; Boens, N.; Dehaen, W. (Angew. Chem., Int. Ed., 2015)

(untitled) - Chong, H.; Lin, H.-A.; Shen, M.-Y.; Liu, C.-Y.; Zhao, H.; Yu, H.-h. (Org. Lett., 2015)

(untitled) - Ni, Y.; Lee, S.; Son, M.; Aratani, N.; Ishida, M.; Samanta, A.; Yamada, H.; Chang, Y.-T.; Furuta, H.; Kim, D.; Wu, J. (Angew. Chem., Int. Ed., 2016)

(untitled) - Patalag, L. J.; Jones, P. G.; Werz, D. B. (Angew. Chem., Int. Ed., 2016)

(untitled) - Hölttä-Vuori, M.; Uronen, R.-L.; Repakova, J.; Salonen, E.; Vattulainen, I.; Panula, P.; Li, Z.; Bittman, R.; Ikonen, E. (Traffic, 2008)

(untitled) - Osati, S.; Ali, H.; van Lier, J. E. (J. Porphyrins Phthalocyanines, 2016)

(untitled) - Lv, H.-j.; Zhang, X.-t.; Wang, S.; Xing, G.-w. (Analyst, 2017)

(untitled) - Li, Z.; Mintzer, E.; Bittman, R. (J. Org. Chem., 2006)

(untitled) - Malachowska-Ugarte, M.; Sperduto, C.; Ermolovich, Y. V.; Sauchuk, A. L.; Jurášek, M.; Litvinovskaya, R. P.; Straltsova, D.; Smolich, I.; Zhabinskii, V. N.; Drašar, P.; Demidchik, V.; Khripach, V. A. (Steroids, 2015)

(untitled) - Jurášek, M.; Rimpelová, S.; Pavlíčková, V.; Ruml, T.; Lapčík, O.; Drašar, P. B. (Steroids, 2015)

(untitled) - Fishkin, N. (Mol. Pharmaceutics, 2015)

(untitled) - Seo, T. S.; Bai, X.; Ruparel, H.; Li, Z.; Turro, N. J.; Ju, J. (Proc. Natl. Acad. Sci. U. S. A., 2004)

(untitled) - Tram, K.; Twohig, D.; Yan, H. (Nucleosides, Nucleotides Nucleic Acids, 2011)

(untitled) - Ehrenschwender, T.; Wanninger-Weiß, C.; Wagenknecht, H.-A. (Nucleic Acids Symp. Ser., 2008)

(untitled) - Ni, Y.; Wu, J. (Org. Biomol. Chem., 2014)

(untitled) - Niu, L.-Y.; Li, H.; Feng, L.; Guan, Y.-S.; Chen, Y.-Z.; Duan, C.-F.; Wu, L.-Z.; Guan, Y.-F.; Tung, C.-H.; Yang, Q.-Z. (Anal. Chim. Acta, 2013)

(untitled) - Feng, L.; Li, H.; Niu, L.-Y.; Guan, Y.-S.; Duan, C.-F.; Guan, Y.-F.; Tung, C.-H.; Yang, Q.-Z. (Talanta, 2013)

(untitled) - Boens, N.; Leen, V.; Dehaen, W. (Chem. Soc. Rev., 2012)

(untitled) - Kamkaew, A.; Lim, S.-H.; Lee, H. B.; Kiew, L. V.; Chung, L. Y.; Burgess, K. (Chem. Soc. Rev., 2013)

(untitled) - Caruso, E.; Banfi, S.; Barbieri, P.; Leva, B.; Orlandi, V. T. (J. Photochem. Photobiol., B, 2012)

(untitled) - Gibbs, J. H.; Zhou, Z.; Kessel, D.; Fronczek, F. R.; Pakhomova, S.; Vicente, M. G. H. (J. Photochem. Photobiol., B, 2015)

(untitled) - Søhoel, H.; Lund Jensen, A.-M.; Møller, J. V.; Nissen, P.; Denmeade, S. R.; Isaacs, J. T.; Olsen, C. E.; Christensen, S. B. (Bioorg. Med. Chem., 2006)

(untitled) - Wictome, M.; Khan, Y. M.; East, J. M.; Lee, A. G. (Biochem. J., 1995)

(untitled) - Jurášek, M.; Džubák, P.; Rimpelová, S.; Sedlák, D.; Konečný, P.; Frydrych, I.; Gurska, S.; Hajdúch, M.; Bogdanová, K.; Kolář, M.; Müller, T.; Kmoníčková, E.; et al. (Steroids, 2017)

(untitled) - Jurášek, M.; Rimpelová, S.; Kmoníčková, E.; Drašar, P.; Ruml, T. (J. Med. Chem., 2014)

(untitled) - Kmoníčková, E.; Harmatha, J.; Vokáč, K.; Kostecká, P.; Farghali, H.; Zídek, Z. (Fitoterapia, 2010)

(untitled) - Yan, J.; Huang, N.; Li, S.; Yang, L.-M.; Xing, W.; Zheng, Y.-T.; Hu, Y. (Bioorg. Med. Chem. Lett., 2012)

(untitled) - Bai, M.; Huang, J.; Zheng, X.; Song, Z.; Tang, M.; Mao, W.; Yuan, L.; Wu, J.; Weng, X.; Zhou, X. (J. Am. Chem. Soc., 2010)

(untitled) - Rega, M.; Jiménez, C.; Rodriguez, J. (Steroids, 2007)

(untitled) - Rostovtsev, V. V.; Green, L. G.; Fokin, V. V.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2002)

(untitled) - Hein, J. E.; Tripp, J. C.; Krasnova, L. B.; Sharpless, K. B.; Fokin, V. V. (Angew. Chem., Int. Ed., 2009)

(untitled) - Mariotto, S.; Menegazzi, M.; Suzuki, H. (Curr. Pharm. Des., 2004)

(untitled) - Rahat, M. A.; Hemmerlein, B. (Front. Physiol., 2013)

(untitled) - Kmoníčková, E.; Melkusová, P.; Harmatha, J.; Vokáč, K.; Farghali, H.; Zídek, Z. (Eur. J. Pharmacol., 2008)

(untitled) - Harmatha, J.; Buděšínský, M.; Vokáč, K.; Kostecká, P.; Kmoníčková, E.; Zídek, Z. (Fitoterapia, 2013)

(untitled) - Tomanová, P.; Rimpelová, S.; Jurášek, M.; Buděšínský, M.; Vejvodová, L.; Ruml, T.; Kmoníčková, E.; Drašar, P. B. (Steroids, 2015)